Talk like TED : - Gallo, Carmine (NY Macmillan Audio, 2014)
Public speaking coach and bestselling author Carmine Gallo has broken down hundreds of TED talks and interviewed the most popular TED presenters, as well as the top researchers in the fields of psychology, communications, and neuroscience to reveal the nine secrets of all successful TED presentations. Gallo's step-by-step method makes it possible for anyone to deliver a presentation that is engaging, persuasive, and memorable.